Preparation and characterization of biodegradable polyacrylic acid based hydrogel for agricultural application - Laftah, Waham Ashaier (2013)
In this study, the influences of different plant natural fibres (PNF) on the properties of poly (acrylic acid) (PAA) based hydrogel were investigated. Polymer hydrogel composites (PHGCs) of poly (acrylic acid) grafted microfibre of cotton (CTN) and oil palm empty fruit bunch (OPEFB) were successfully prepared using solution polymerization technique. Surface methodology and central composite design (CCD) were used to optimize the best content of the initiator (APS), cross-linker (MBA), neutralizer (NaOH) and plant natural microfibres (CTN, OPEFB). The functional groups of PHGs were characterized using Fourier Transform Infrared (FTIR). The effects of CTN and OPEFB on swelling rate, re-swelling capability, thermal, mechanical, biodegradation properties were investigated. Morphological study of PHGs was carried out using Scanning Electron Microscopy (SEM). The effect of PHGs on soil holding capacity, urea leaching loss rate (ULLR) and red okra plant growth were evaluated. The average optimum content of APS, MBA, NaOH and natural fibre were 1.3-1.6, 0.15-0.16, 11.9-14.6 and 13.9-15 wt. % respectively. SEM images indicated that the polymer hydrogel grafted CTN fibre has bigger pore size than that of polymer hydrogel grafted OPEFB fibre and plain PHG. PHGs grafted natural fibres showed higher thermal stability, mechanical properties, biodegradation, swelling rate and re-swelling capability compared to plain polymer hydrogel. Polymer hydrogel grafted micro natural fibre of high cellulose content (CTN) has superior properties compared to that of grafted with microfibre of less cellulose content (OPEFB) and plain polymer hydrogel. Polymer hydrogel composites as soil conditioner and slow release system have positive effect on the holding capacity of sandy soil, ULLR and consequently on red okra plant growth.